The concept of deep communication and neo-Protestant theology - Strelkova, Julia (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2018)
In this article we are trying to present basic ideas of exponents of neo-protestant theology, which con-cerns views on problematics of human communication. We are exploring the ideas of E. Brunner, F. Gogarten and D. Bonhoffer. These ideas are so remarkable for creating the integral conception of Christian neo-orthodoxy and making more profound our philosophical insights about existential and ontological aspects of inter-personal communication